Break Even Point Analysis As a Tool For Profit And Sales Planning On Otak-Otak Bandeng Kang Wahab SME - Nisfatur Rizki; Agus Sukoco (Journal of World Conference (JWC), 2019)
This study aims to determine break-even point and margin of safety and how to plan profits and sales by using Break Even Point Analysis on Otak-Otak Kang Wahab SME. The method used in this study is qualitative descriptive with a case study research approach, by conducting direct interviews with the owner. Analysis have been carried out using Break Even Point Analysis. The data being analyzed in this study are production and non-production reports, product prices, sales volumes and costs. The results show that the sales of SME product which have been analyzed through Break Even Point have break-even point after it reachs 1 months 10 days, with revenue of Rp. 270,309,375 and selling of 2,809 units. Margin of Safety is known to be 82%. In this case, the SME don‘t include asset investments in the form of business places, because they use their own residence, so the cost isn’t considered.